A two‐component enzyme complex is required for dolichol biosynthesis in tomato. (26th May 2015) - Brasher, Megan I.; Surmacz, Liliana; Leong, Bryan; Pitcher, Jocelyn; Swiezewska, Ewa; Pichersky, Eran; Akhtar, Tariq A.
Summary: Dolichol plays an indispensable role in the N ‐glycosylation of eukaryotic proteins. As proteins enter the secretory pathway they are decorated by a 'glycan', which is preassembled onto a membrane‐anchored dolichol molecule embedded within the endoplasmic reticulum (ER). Genetic and biochemical evidence in yeast and animals indicate that a cis ‐prenyltransferase (CPT) is required for dolichol synthesis, but also point to other factor(s) that could be involved. In this study, RNAi‐mediated suppression of one member of the tomato CPT family (SlCPT3) resulted in a ~60% decrease in dolichol content. We further show that the involvement of SlCPT3 in dolichol biosynthesis requires the participation of a distantly related partner protein, designated as CPT‐binding protein (SlCPTBP), which is a close homolog of the human Nogo‐B receptor. Yeast two‐hybrid and co‐immunoprecipitation assays demonstrate that SlCPT3 and its partner protein interact in vivo and that both SlCPT3 and SlCPTBP are required to complement the growth defects and dolichol deficiency of the yeast dolichol mutant, rer2∆ . Co‐expression of SlCPT3 and SlCPTBP in yeast and in E .  coli confirmed that dolichol synthase activity strictly requires both proteins. Finally, organelle isolation and in vivo localization of fluorescent protein fusions showed that both SlCPT3 and SlCPTBP localize to the ER, the site of dolichol accumulation and synthesis in eukaryotes. Significance Statement: While considered physiologically indispensable, dolichol biosynthesis in plants remains poorly understood. In this study we provide evidence in yeast, E. coli and in plants that a member of the tomato cis‐prenyltransferase (CPT) family and a distantly related CPT‐like protein interact to form a 'dolichol synthase'.